The Role of Brain-Derived Neurotrophic Factor Signaling in Central Nervous System Disease Pathogenesis - Dou, Shu-Hui; Cui, Yu; Huang, Shu-Ming; Zhang, Bo (Frontiers in Human Neuroscience, 2022)
Recent studies have found abnormal levels of brain-derived neurotrophic factor (BDNF) in a variety of central nervous system (CNS) diseases (e.g., stroke, depression, anxiety, Alzheimer’s disease, and Parkinson’s disease). This suggests that BDNF may be involved in the pathogenesis of these diseases. Moreover, regulating BDNF signaling may represent a potential treatment for such diseases. With reference to recent research papers in related fields, this paper reviews the production and regulation of BDNF in CNS and the role of BDNF signaling disorders in these diseases. A brief introduction of the clinical application status of BDNF is also provided.